2022
DOI: 10.3390/molecules28010309
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Synthesis of Mannich Adducts from 1,4-Naphthoquinones and Profile as Autophagic Inducers in Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is a worldwide public health problem, accounting for approximately 90% of all oral cancers, and is the eighth most common cancer in men. Cisplatin and carboplatin are the main chemotherapy drugs used in the clinic. However, in addition to their serious side effects, such as damage to the nervous system and kidneys, there is also drug resistance. Thus, the development of new drugs becomes of great importance. Naphthoquinones have been described with antitumor activity. Some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Also, tellurium-derived compounds, especially the compound ( 10a ), showed an increased antineoplastic potential with sufficient selectivity in relation to nontumor cells. Since OSSC still presents itself as a challenging malignancy for effective treatment, , several studies are being conducted to evaluate new synthetic or derivatives of natural compounds to improve OSSC prognosis and reduce chemotherapy comorbidities. , Considering the promising results obtained in terms of synthesis, yields, antiproliferative activity, cell migration inhibition, induction of cell death, and low toxicity, this work suggests the potential of the compound ( 10a ) as a promising antineoplastic agent for further study.…”
Section: Resultsmentioning
confidence: 99%
“…Also, tellurium-derived compounds, especially the compound ( 10a ), showed an increased antineoplastic potential with sufficient selectivity in relation to nontumor cells. Since OSSC still presents itself as a challenging malignancy for effective treatment, , several studies are being conducted to evaluate new synthetic or derivatives of natural compounds to improve OSSC prognosis and reduce chemotherapy comorbidities. , Considering the promising results obtained in terms of synthesis, yields, antiproliferative activity, cell migration inhibition, induction of cell death, and low toxicity, this work suggests the potential of the compound ( 10a ) as a promising antineoplastic agent for further study.…”
Section: Resultsmentioning
confidence: 99%
“…The initial screening was performed in SCC9 cells because it is usually more sensitive to anticancer drugs [ 31 ]. However, to restrict possible abnormalities in the behavior of a single cell line when compared with cancer cells in patients it is important to consider other oral cancer cell lines, as well as determining whether the effect is general or cancer specific.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, the 1,2,3-triazole ring was proven to be a pharmacophore [ 22 , 23 ]. In recent years, we have reported natural flavonoids, terpenes, lignans [ 24 , 25 , 26 , 27 ], and also some synthetic naphthoquinones, as Ia–c ( Scheme 1 ), with significant activity against human OSCC [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Borges et al 2023, studied the role of 16 naphthoquinones, which inhibits PKM2 to induce autophagy via PI3K/Akt pathway and its associated apoptosis. It was concluded, that the compound 6a was the most potent drug used in the treatment of cancer and was well tolerated by the animals, extremely selective and had promising pharmacokinetic properties 51 . Wen et al 2023, reported that Rho-associated protein kinase (ROCK) inhibitor Y-27632 modulated Akt/mTOR pathway to induce autophagy and further tumour progression.…”
Section: Pi3k/akt Autophagy In Oral Squamous Cell Carcinomamentioning
confidence: 99%